Emergency department crowding and length of stay before and after an increased catchment area - Mentzoni, Ida (BMC Health Serv Res, 2019)
BACKGROUND: Emergency department (ED) crowding and prolonged length of stay (LOS) are associated with delays in treatment, adverse outcomes and decreased patient satisfaction. Hospital restructuring and mergers are often associated with increased ED crowding. The aim of this study was to explore ED crowding and LOS in Norway’s largest ED before and after an increased catchment area. METHODS: The catchment area of Akershus University Hospital increased by approximately 150,000 inhabitants in 2011, from 340,000 to 490,000. In this retrospective study, admissions to the ED during a six-year period, from Jan 1st 2010 to Dec 31st 2015 were included and analyzed. RESULTS: A total of 179,989 admissions were included (51.0% men). The highest occupancy rate was in the age group 70–79 years. Following the increase in the catchment area, the annual ED admissions increased by 8343 (40.9%) from 2010 to 2011, and peaked in 2013 (34,002). Mean LOS increased from 3:59 h in 2010 to 4:17 in 2012 (highest), and decreased to 3:45 h in 2015 after staff, capacity and organizational measures. In 2010, 37.9% of the ED patients experienced crowding, and this proportion increased to between 52.9–77.6% in 2011–2015. Crowding peaked between 4 and 5 PM. CONCLUSIONS: LOS increased and crowding was more frequent after a major increase in the hospital’s catchment area in Norway’s largest emergency department. Even after 5 years, the LOS was higher than before the expansion, mainly because of the throughput and output components, which were not properly adapted to the changes in input. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12913-019-4342-4) contains supplementary material, which is available to authorized users.